REVIEWING THE INDO-PACIFIC POLICY OF FRANCE: CAN GAULLISM SHINE, AND HOW? (Journal of International Studies, 2024)
In the context of escalating global geopolitical concerns over the Indo-Pacific region, France stands out among its European counterparts for being the earliest state to recognize the region’s significance. This distinction has prompted key research questions in the following three areas: the motivation behind France’s Indo-Pacific policy, whether France’s actions deviate from its Gaullist foreign policy tradition, and the potential effectiveness of these actions. To address these questions, this paper conducted a careful qualitative examination of France’s Indo-Pacific policy development and characteristics. The findings revealed that France’s Indo-Pacific policy is motivated by three key interests, namely security, economy, and leadership. This paper also found that France’s policy actions reflected both a continuation and modification of the Gaullist tradition, evident in President Macron’s mix of cooperation and skepticism toward the United States (US) and North Atlantic Treaty Organization. Concerning policy effectiveness, France’s status as a regional and middle power implies significant constraints in its physical capabilities, which hinder its ability to alleviate tension arising from the US–China competition, the dominant forces shaping the regional political-economic dynamics. Nevertheless, France’s expanding presence and enhanced softpower influence in the Indo-Pacific region have the potential to yield increased bargaining leverage in its interaction with the US and China.